POPULASI DAN AKTIVITAS DENITRIFIKASI SERTA EMISI GAS N2O PADA LAHAN PERTANIAN ORGANIK, PERTANIAN INTENSIF, DAN HUTAN - Dwi Agustiyani; Nur Laili; Hartati Imamuddin; Nunik Sulistinah (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
This research investigate the population and potentials denitrification activity from three different soils, organically farmed soil, intensive farmed soil and forest soil. Our objectives were to explore spatial gradients in denitrifier populations, examine whether populations density and its potential activity was related to soil chemical properties (C and N content), and determine the potential emission of gas N2O. Results indicated biological functional differences between these three different soil ecosystems. Forest soil had the highest population density of denitrifying bacteria and also had significant potential denitrifying activities. The highest potentials denitrifying activity in the soil affected to the lowest emission of N2O gas. The lowest population and potential denitrifying activity was measured in the intensive farmed soil. Those conditions might be promoted the potentials emission of N2O.